Riccatis Equation. Asymptotics of Exact Solution - Tsapenko, Nikolai Evgenievich (International Journal of Mathematical Research, 2016)
In this article based on a method of approximating equation an asymptotic solution of the general Riccati ‘s equation is obtained. The principal distinctive feature and advantage of the solution is its continuity at turning points. Estimates of accuracy of the approximate solution are derived. Limit values of the asymptotic solution in case of one-sided convergence of argument to turning point of the first order are calculated.